a solucao da equacao : 3(x+ 4) + 5(x + 2) = 3x + 12 e igual a a) s= {-2 } b) s= { 2 } c) s= { -3 } d) s= { 3 } e) s= {-4 }
Soluções para a tarefa
Respondido por
0
Resposta:
s={-2}
Explicação passo-a-passo:
3(x + 4) + 5(x + 2) = 3x + 12
3x + 12 + 5x + 10 = 3x + 12
3x + 5x - 3x = 12 - 12 -10
5x = -10
-10
x = ------ = -2
5
Respondido por
0
Resposta:
3(x+4)+5(x+2)=3x+12
3×+12+5x+10=3x+12
3x+5x-3x=12-12+10
5x=10
x=10/5
x=2
Resposta b
Perguntas interessantes
Matemática,
10 meses atrás
Geografia,
10 meses atrás
Matemática,
10 meses atrás
Física,
1 ano atrás
Português,
1 ano atrás
Química,
1 ano atrás